MODELLING THE SPREAD OF DENGUE IN A HUMAN POPULATION IN NATIONAL CAPITAL REGION (NCR), PHILIPPINES USING THE SIR (SUSCEPTIBLE-INFECTED-RECOVERED), SEIR (SUSCEPTIBLE-EXPOSED-INFECTED-RECOVERED), AND SIR WITH VERTICAL TRANSMISSION MODELS - Aragoza, Ian Angelo T.; Santos, King Arthur M.; Maliwat, Nyle Aldrin S.; Bueno, Aldous Cesar F. (Journal of Technology Management and Business, 2018)
The unimpeded growth of urban population has unfortunately paved way to spreading multiple infectious diseases that greatly puts a population the risk of incurring an outbreak had the spread of disease not been managed well. Dengue is a major contagious disease that has been plaguing the world ever since, and epidemic outbreaks trying to be mitigated and minimized by researchers. One way to predict the pattern of the disease on a macro scale is to use mathematical models to understand the dynamics of the epidemics caused by the disease. This study uses the SIR, SEIR, and SIR with Vertical Transmission to model the spread of dengue in NCR, Philippines within the year 2010. Afterwards, each model was then used to simulate two disease control methods: Constant Vaccination Strategy (CVS) and Quarantine, which controls the infection and recovery rate parameters with SIR with linear parameters having the highest accuracy among all the models the R2 value being 0.99683. The created models are accurate hence can be used to simulate dengue dynamics in NCR. CVS and Quarantine substantially decreased the peak of the epidemic for all models, confirming those methods as effective deterrents dengue incidence